2022
DOI: 10.29407/js_unpgri.v8i2.17748
|View full text |Cite
|
Sign up to set email alerts
|

Audio-visual teaching materials supporting tennis

Abstract: The process of learning tennis skills begins with the cognitive, associative, and automation stages. The cognitive stage is the most basic stage, so it is necessary to identify student learning styles at this stage. The learning styles that are widely used at the cognitive stage are visual and auditory learning styles. Teaching materials in the form of audio-visual can facilitate student learning styles at the cognitive stage. This research aims to develop audio-visual teaching materials for teaching tennis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The use of the field tennis trainer model media in tennis training can facilitate the understanding and strengthen athletes' ball fealing by understanding the material in the field tennis trainer model relating activities in the daily lives of athletes Agustiyanto, (2023). This is in line with the findings of previous researchers who showed that the court tennis trainer model media has met the criteria for use as a training medium (Falcão et al, 2020;Raibowo et al, 2022). coaches (Afendi et al, 2021;Amni et al, 2019;Sitompul, 2020).…”
Section: ) Measurements Expertsupporting
confidence: 91%
See 3 more Smart Citations
“…The use of the field tennis trainer model media in tennis training can facilitate the understanding and strengthen athletes' ball fealing by understanding the material in the field tennis trainer model relating activities in the daily lives of athletes Agustiyanto, (2023). This is in line with the findings of previous researchers who showed that the court tennis trainer model media has met the criteria for use as a training medium (Falcão et al, 2020;Raibowo et al, 2022). coaches (Afendi et al, 2021;Amni et al, 2019;Sitompul, 2020).…”
Section: ) Measurements Expertsupporting
confidence: 91%
“…Almost all beginner tennis players who learn the game of tennis have difficulties, so the game of tennis is often classified into difficult and complex types of skills. As revealed (Raibowo et al, 2020) tennis games are influenced by other people or the presence of environmental factors that are difficult to control. Furthermore, according to (Cahyadi et al, 2019), difficulties in mastering tennis skills occur because tennis players, when playing, will never receive or hit the ball in the exact same place but always move around where the ball falls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations